Socio-Economic Analysis of Two Pot Raised Mud Improved Cookstove in the Context of Nepal - Darlami, Hari Bahadur; Ale, Bhakta Bahadur; Pokharel, Govind Raj (Journal of Advanced College of Engineering and Management, 2022)
Cost Biomass cookstove is extensively used for cooking and space heating in the rural area of Nepal. Its thermal efficiency and emission performance keeps prominence economically, socially and environmentally. Chimney operated two pot raised mud Improved Cookstove (ICS) is one of the most promoted cookstoves in the context of Nepal. Benefit cost ratio has been found maximum for geometrically optimized best dimension cookstove and minimum for grate and insulation used cookstove in best dimension. Net benefit of cookstove has been increased with the grate and insulation. Marginal abatement cost of best dimension cookstove has been found minimum NPR. 445/tCO2eq and maximum for the cookstove with the use all the accessories NPR 600 tCO2eq. Best dimension cooostove has been found best rank from benefit cost ratio and abatement cost aspect. The goal of this study is to perform socio-economic and environmental analysis of the twopot raised mud ICS for three family members.